2012
DOI: 10.1128/jvi.06671-11
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Analysis of Viruses from Bat Fecal Samples Reveals Many Novel Viruses in Insectivorous Bats in China

Abstract: bIncreasing data indicate that bats harbor diverse viruses, some of which cause severe human diseases. In this study, sequenceindependent amplification and high-throughput sequencing (Solexa) were applied to the metagenomic analysis of viruses in bat fecal samples collected from 6 locations in China. A total of 8,746,417 reads with a length of 306,124,595 bp were obtained. Among these reads, 13,541 (0.15%) had similarity to phage sequences and 9,170 (0.1%) had similarity to eukaryotic virus sequences. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

18
192
9
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(221 citation statements)
references
References 49 publications
18
192
9
2
Order By: Relevance
“…Compared with the viral communities found among mosquitoes and bats by approaches similar to those used in this study (13,18,25,107,108), the diversity of viruses found in this agricultural pest insect was much lower. Obviously, host range of the target sampled can play an important role in the diversity of viral sequences detected.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Compared with the viral communities found among mosquitoes and bats by approaches similar to those used in this study (13,18,25,107,108), the diversity of viruses found in this agricultural pest insect was much lower. Obviously, host range of the target sampled can play an important role in the diversity of viral sequences detected.…”
Section: Discussioncontrasting
confidence: 52%
“…Samples were collected in different geographic locations and at different times and probably reflect different ages of D. citri. We also do not know enough about the genetic diversity among the D. citri populations studied here, and it has been demonstrated that the viromes of mosquitoes and bats vary by species, age, space, time, and sample type (13,107).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…With high-throughput next-generation sequencing technology, viral metagenomics have been successfully used to explore the bat virome, leading to the discovery of many novel viruses in the last 4 years, such as bat circovirus, bat papillomavirus, bat bocavirus, bat astrovirus, and bat hepatitis virus (13)(14)(15)(16)(17)(18). Esona and colleagues first reported a partial genomic sequence of an RVA strain from straw-colored fruit bats in Africa in 2010 (19).…”
mentioning
confidence: 99%
“…In this study, certain viruses have been screened inside whole specimens of ticks collected from stockyard areas 50 km east and west of Riyadh, Capital of Saudi Arabia. Results of this study may reflect the diets of ticks [29].…”
Section: Discussionmentioning
confidence: 82%